Bradycardia During Targeted Temperature Management: An Early Marker of Lower Mortality and Favorable Neurologic Outcome in Comatose Out-of-Hospital Cardiac Arrest Patients*. Issue 2 (February 2016) - Thomsen, Jakob Hartvig; Nielsen, Niklas; Hassager, Christian; Wanscher, Michael; Pehrson, Steen; Køber, Lars; Bro-Jeppesen, John; Søholm, Helle; Winther-Jensen, Matilde; Pellis, Tommaso; Kuiper, Michael; Erlinge, David; et al.
Abstract : Objectives: Bradycardia is common during targeted temperature management, likely being a physiologic response to lower body temperature, and has recently been associated with favorable outcome following out-of-hospital cardiac arrest in smaller observational studies. The present study sought to confirm this finding in a large multicenter cohort of patients treated with targeted temperature management at 33°C and explore the response to targeted temperature management targeting 36°C. Design: Post hoc analysis of a prospective randomized study. Setting: Thirty-six ICUs in 10 countries. Patients: We studied 447 (targeted temperature management = 33°C) and 430 (targeted temperature management = 36°C) comatose out-of-hospital cardiac arrest patients with available heart rate data, randomly assigned in the targeted temperature management trial from 2010 to 2013. Interventions: Targeted temperature management at 33°C and 36°C. Measurements and Main Results: Endpoints were 180-day mortality and unfavorable neurologic function (cerebral performance category 3–5). Patients were stratified by target temperature and minimum heart rate during targeted temperature management (< 50, 50–59, and ≥ 60 beats/min [reference]) at 12, 20, and 28 hours after randomization. Heart rates less than 50 beats/min and 50–59 beats/min were recorded in 132 (30%) and 131 (29%) of the 33°C group, respectively. Crude 180-day mortality increased with increasing minimum heart rate (< 50 beats/min = 32%, 50–59 beats/min = 43%, and ≥ 60 beats/min = 60%; p log-rank < 0.0001). Bradycardia less than 50 beats/min was independently associated with lower 180-day mortality (hazard ratioadjusted = 0.50 [0.34–0.74; p < 0.001]) and lower odds of unfavorable neurologic outcome (odds ratioadjusted = 0.38 [ 0.21–0.68; p < 0.01]) in models adjusting for potential confounders including age, initial rhythm, time to return of spontaneous circulation, and lactate at admission. Similar, albeit less strong, independent associations of lower heart rates and favorable outcome were found in patients treated with targeted temperature management at 36°C. Conclusions: This study confirms an independent association of bradycardia and lower mortality and favorable neurologic outcome in a large cohort of comatose out-of-hospital cardiac arrest patients treated by targeted temperature management at 33°C. Bradycardia during targeted temperature management at 33°C may thus be a novel, early marker of favorable outcome. Abstract : Supplemental Digital Content is available in the text.